(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Vulval lipomas are rare benign mesenchymal tumours consisting of mature fat cells, often interspersed with strands of fibrous connective tissue. Arising from the vulvar fotty pads, they present as soft, multiloculated subcutaneous neoplasms. Their occurrence in the valve is said to be so rare that only a few cases have been reported. We present a rare case of a giant lipoma in the vulva. Case Report: This is the case report of a 65-year-old postmenopausal lady with a slowly growing mass in her vulva for about 10 years. After thorough clinical examination and laboratoryinvestigation, the mass was excised and histopathological report revealed vulvallipoma. Conclusion: Vulvallipoma is rare and so must be differentiated from other benign cystic swelling and malignant neoplasm in the vulva. The final diagnosis should be based on histopathological evaluation. JCMCTA 2020 ; 31 (2) : 149-151